Evaluasi Kepuasan Pengguna Menggunakan Model End User Computing Satisfaction (EUCS) Pada Valery (Virtual Resources Library) Perpustakaan Universitas Bandar Lampung - Putry, Dhea Nabella; Kesuma, Mezan el Khaeri; Yunita, Irva; Amaliah, Eni (Institut Agama Islam Negeri (IAIN) Curup, 2025)
By using the End User Computing Satisfaction (EUCS) paradigm, EUCS is a model or method used to measure the level of user satisfaction with an information system by considering several indicators such as content, accuracy, format, ease and timeliness. This study attempts to assess the level of user satisfaction with Valery , a virtual resource library at the Bandar Lampung University Library that has a unique voice feature that makes it interesting to study. By using quantitative techniques, this study is descriptive. In this study, 88 participants were surveyed. Information was collected using a survey using a Likert scale. This study uses the mean and grand mean formulas for data analysis. Finally, the evaluation findings are presented on an interval scale. By using the End User Computing Satisfaction (EUCS) model, the Bandar Lampung University Library evaluated Valery , a virtual resource library, and found that users were generally satisfied with its system with an average score of 4.51. By using the End User Computing Satisfaction (EUCS) model, Valery (Virtual Resources Library) of Bandar Lampung University Library received a